2019
DOI: 10.1002/jcb.28874
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 32 promotes cell proliferation, migration, and suppresses apoptosis in colon cancer cells by targeting OTU domain containing 3

Abstract: Colorectal cancer is considered as the fourth leading reason of cancer‐linked deaths worldwide. However, our knowledge about its pathogenic mechanism remains inadequate. MicroRNA 32 (miR‐32), a member of small noncoding RNAs, has been found vital roles in tumorigenesis. This study studied its functions and underlying mechanism in colorectal cancer. The experiment revealed the obvious upregulation of miR‐32 in colorectal cancer tissues and six cancer cell lines, compared with normal tissues and cells. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…For example, relevant studies found that miR-181a can promote angiogenesis in CRC tissues by regulating SRCIN1 so that SRC/VEGF signaling pathway can be promoted [ 12 ]. Jin Y et al observed that miR-32 plays a key role in cell proliferation and migration, as well as in suppressing apoptosis in colon cancer [ 13 ]. These studies further enhance the essential roles of microRNAs in cancer and the necessity of identifying novel CRC biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, relevant studies found that miR-181a can promote angiogenesis in CRC tissues by regulating SRCIN1 so that SRC/VEGF signaling pathway can be promoted [ 12 ]. Jin Y et al observed that miR-32 plays a key role in cell proliferation and migration, as well as in suppressing apoptosis in colon cancer [ 13 ]. These studies further enhance the essential roles of microRNAs in cancer and the necessity of identifying novel CRC biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…The miR-32 inhibited apoptosis by directly targeting OTUD3 in colon cancer cells. The miR-32 upregulation reduced cell apoptosis, while its downregulation displayed opposite effects [ 103 ]. The decrease in FAS expression could contribute to the reduction of apoptosis in CRC cells.…”
Section: Mirna In Apoptosis Of Colorectal Cancermentioning
confidence: 99%
“…Recent studies showed that OTU deubiquitinases can act as either positive or negative regulators in different types of cancer. For instance, OTU deubiquitinase 3 (OTUD3) expression level decreases directly via microRNA-32 targeting, which leads to enhanced proliferation in the HCT116 colorectal cell line [89]. On the other hand, the overexpression of ubiquitin aldehyde binding 1 (OTUB1) was detected in colorectal cancer tissues, which induced the metastasis both in vivo and in vitro studies via triggering the epithelial-mesenchymal transition [90].…”
Section: Compounds Targeted E2 Enzymementioning
confidence: 99%